Dig Houses, Dwelling, and Knowledge Production in Archaeology. (10th March 2015) - Morgan, Colleen; Eddisford, Daniel
Abstract : Dig houses are where archaeologists dwell during excavations. These accommodations vary as broadly as their accompanying archaeological sites and are integral to the experience of archaeological investigation. Even as interest in embodied approaches to archaeology become popular, dig houses remain invisible in academic literature. In this article we examine the impact of the lived environment on archaeological research. To provide context to this study, we briefly discuss the history of dig houses in archaeological practice, then describe modern accommodations used during excavations. Building on this background, we then review phenomenological and architectural approaches to understanding the impact of the built environment on academic research. This understanding will then be used for a specific case study—the life-history of a small building called the "Chicken Shed" at Çatalhöyük. Finally, we discuss the conclusions of our research: how dig houses impact the construction of the past and how to situate them as places to think, collaborate, and critique archaeological practice.